2023
DOI: 10.1111/nyas.15063
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in surface wind speed projections over the Iberian Peninsula: CMIP6 GCMs versus a WRF‐RCM

Miguel Andres‐Martin,
Cesar Azorin‐Molina,
Cheng Shen
et al.

Abstract: This study assessed the projected near‐surface wind speed (SWS) changes and variability over the Iberian Peninsula for the 21st century. Here, we compared Coupled Model Intercomparison Project Phase 6 global climate models (GCMs) with a higher spatial resolution regional climate model (RCM; ∼20 km), known as WRF‐CESM2, which was created by a dynamic downscaling of the Community Earth System Model version 2 (CESM2) using the Weather Research and Forecasting (WRF) model. Our analysis found that the GCMs tended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…CMIP6 models are considered more realistic in simulating historical wind energy resources compared to CMIP5 models (Carvalho et al, 2021). Although most models can reasonably reproduce the observed climatology of near-surface wind speed (NSWS), they fail to capture the longterm trend (Andres-Martin et al, 2023). Shen et al (2022) found that CMIP6 models cannot reproduce the observed trend of terrestrial NSWS, while there are no studies that have investigated if the CMIP5/CMIP6 models can reproduce the global offshore NSWS trend as far as we know.…”
Section: Introductionmentioning
confidence: 99%
“…CMIP6 models are considered more realistic in simulating historical wind energy resources compared to CMIP5 models (Carvalho et al, 2021). Although most models can reasonably reproduce the observed climatology of near-surface wind speed (NSWS), they fail to capture the longterm trend (Andres-Martin et al, 2023). Shen et al (2022) found that CMIP6 models cannot reproduce the observed trend of terrestrial NSWS, while there are no studies that have investigated if the CMIP5/CMIP6 models can reproduce the global offshore NSWS trend as far as we know.…”
Section: Introductionmentioning
confidence: 99%